PERLINDUNGAN HUKUM TERHADAP KONSUMEN PADA PEMADAMAN LISTRIK SEPIHAK OLEH PT PLN (PERSERO) MENURUT UNDANG UNDANG NO 8 TAHUN 1999 - Apriyanti Ritonga, Nurul Hidayah; Syam, Syafruddin (Universitas Ekasakti, 2023)
This research was conducted with the aim of knowing how to protect electricity consumers in Law no. 8 of 1999 concerning Consumer Protection and Law no. 30 of 2009 concerning Electricity and how legal remedies can be taken by electricity consumers in the event of a unilateral power outage by PT. PLN (Persero). By using normative juridical research methods, it can be concluded: 1. Protection of electricity consumers has been protected by the Government in Law Number 8 of 1999 concerning Consumer Protection and Law Number 30 of 2009 concerning Electricity. The Consumer Protection Act states that consumers have the right to convenience, security and safety in consuming goods and/or services. Meanwhile, the Electricity Law states that consumers have the right to receive electricity continuously with good quality and reliability. So it is the obligation of PT PLN (Persero) as the holder of a business permit for the supply of electricity, to provide electricity that meets the applicable quality and reliability standards. If the power outages that occur are less than the service standards set by the Government, consumers are entitled to compensation from PT PLN (Persero). 2. The initial effort that consumers can take in the event of a unilateral power outage by PT PLN (Persero) is to submit a complaint to PT PLN (Persero).